Synthetic Cationic Autoantigen Mimics Glatiramer Acetate Persistence at the Site of Injection and Is Efficacious Against Experimental Autoimmune Encephalomyelitis - Song, Jimmy Y.; Griffin, J. Daniel; Larson, Nicholas R.; Christopher, Matthew A.; Middaugh, C. Russell; Berkland, Cory J. (Frontiers in Immunology, 2021)
A synthetic peptide, K-PLP, consisting of 11-unit poly-lysine (K11) linked via polyethylene glycol (PEG) to proteolipid protein epitope (PLP) was synthesized, characterized, and evaluated for efficacy in ameliorating experimental autoimmune encephalomyelitis (EAE) induced by PLP. K-PLP was designed to mimic the cationic nature of the relapsing-remitting multiple sclerosis treatment, glatiramer acetate (GA). With a pI of ~10, GA is able to form visible aggregates at the site of injection via electrostatic interactions with the anionic extracellular matrix. Aggregation further facilitates the retention of GA at the site of injection and draining lymph nodes, which may contribute to its mechanism of action. K-PLP with a pI of ~11, was found to form visible aggregates in the presence of glycosaminoglycans and persist at the injection site and draining lymph nodes in vivo, similar to GA. Additionally, EAE mice treated with K-PLP showed significant inhibition of clinical symptoms compared to free poly-lysine and to PLP, which are the components of K-PLP, and GA. The ability of the poly-lysine motif to retain PLP at the injection site, which increased the local exposure of PLP to immune cells may be an important factor affecting drug efficacy.